Bimbingan Kelompok Sebagai Upaya Meningkatkan Kinerja Guru Dalam Membuat Alat Peraga Pembelajaran di SDN 152/X Sungai Sayang Semester Genap Tahun Ajaran 2021/2022 - Subandi Subandi (Departement of Mathematics Education, 2023)
This study aims to obtain information discussing guidance groups as an effort to improve teacher performance in making learning aids at SDN 152/X Sungai Sayang even semester of the 2021/2022 academic year. This research is a school action research which consists of two cycles with each cycle following four stages, namely planning, implementing, observing, and reflecting. This research was conducted at SDN 152/X Sungai Sayang in the even semester of the 2021/2022 school year with 7 research subjects who were class teachers and subject teachers. Data collection techniques using observation, field notes and documentation. Data were analyzed using proportions and data reduction. Based on the results of the research and discussion, it can be interpreted that through group guidance can improve teacher performance in making learning aids at SDN 152/X Sungai Sayang even semester of the 2021/2022 academic year by giving rewards.